2017
DOI: 10.1007/s00244-017-0420-y
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and Exposure Evaluation of Metals in Diverse Food Items from Chengdu, China

Abstract: A total of 520 food samples belonging to 29 food types and 63 drinking water were collected in Chengdu market of China in 2014 to investigate the concentrations of 11 metals, and to assess the related exposure to the local consumers by estimating the hazard quotient and carcinogenic risk (CR). The results showed that metals concentrations in drinking water were below the limit values suggested by the Ministry of Health of the People's Republic of China, and FAO/WHO (Food and Agriculture Organization of the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
2
5
2
Order By: Relevance
“…As the result showed, the HQ dermal contact of Cr determined for more than 63% of HI dermal contact for children. This was consistent with the previous studies; they reported that dermal contact with Cr contributed to higher non-carcinogenic risk compared to other exposure routes [17, 40].…”
Section: Resultssupporting
confidence: 93%
“…As the result showed, the HQ dermal contact of Cr determined for more than 63% of HI dermal contact for children. This was consistent with the previous studies; they reported that dermal contact with Cr contributed to higher non-carcinogenic risk compared to other exposure routes [17, 40].…”
Section: Resultssupporting
confidence: 93%
“…The mean Ni content in chicken in the present study (0.035–0.940 mg/kg) was lower than the values reported in Dareta, Northern Nigeria (1.012 mg/kg) 25. The maximum concentration of Ni obtained in the current study was higher than in previous studies reported by Wang et al (76.5 μg/kg), Zahurul et al (0.491 mg/kg) and Yuanan Hu et al27,32,36…”
Section: Discussioncontrasting
confidence: 72%
“…The chromium concentrations recorded in this study were higher than those reported by Iwegbue et al (0.01–3.43 mg/kg) 4. The mean concentration of Cr (0.032–96.62 mg/kg) was higher than reported in China (0.430 mg/kg, Wang et al and 0.158 mg/kg, Yuanan et al) and in northern Nigeria (2.55 mg/kg, Orisakwe et al 2017) 25,28,32. In general, the concentration of total chromium in meat ranged from 0.01 to 1.3 mg/kg.…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, higher levels of Cu, Zn, Pb, and Cd were found in poultry meat retailed in Sharkia Governorate, Egypt (El-Bayomi et al, 2019). Also, substantially higher ranges of Pb, Cd, Ni, Cu and Cr in chicken meat were reported from Bangladesh (Mottalib et al, 2018), China (Wang et al, 2018), Algeria, (Benouadah et al, 2015).…”
Section: Resultsmentioning
confidence: 96%